Perception of Local People towards Blazing Mountain Due to Forest Fire in Changing Climatic Scenario of Uttarakhand Himalaya: A Need for Scientific Intervention for Sensitization and Conservation and Livelihood Sustainability of Region - Rawat, Neelam; Purohit, Saurabh; Negi, Govind Singh; Pant, Durgesh (Indian Forester, 2017)
Forest Fires strongly affect the distribution and abundance of plant species, habitats of animals and hence landscape properties. Fire, whether natural or anthropogenic, is a widespread and recurring phenomenon in Indian forests. The causes of the forest fires can be classified into three main categories (i) Natural causes, (ii) Intentionally/Deliberately caused by man and (iii) Unintentionally/Accidentally caused by man. Around 90% of the forest fires in India are anthropogenic in nature. Fires strongly affect the distribution and abundance of plant species, habitats of animals and hence landscape properties. The local people and community participation always been considered for management and utilization activity of fire and natural resources. Forest Fires in Uttarakhand have till now been fought with conventional methods. Conventional methods are insufficient and should be coupled with the technological advancements in order to get better fire management strategy. During last two decades scientific world has made considerable advancement in monitoring and warning regarding the outbreak of forest fires with the help of GIS and satellite technology. Beside it the use of these resources should be gear up for sustainable livelihood development. This paper highlight the people perception and how scientific intervention coupled with community approach can be helpful for fire reduction and better utilization of natural forest wealth.